Al-Dhafiri al-Yamani’s position on Ibn Al-Hajib’s opinions in his book Al-Manahil AI-Safia to revealing the healing meanings - Al-Shalili, Amani Zaid Ali; Shamsan, Hadi Abdulla Naji (Journal of Arabic Language Sciences and Literature, 2023)
The aim of this research is to clarify the position of al-Dhafiri al-Yamani’s (T1035AH) on Ibn Al-Hajib’s opinions in his book Al-Manahil AI-Safia to revealing the healing meanings, and through that it appeared that Al-Dhafiri’s position varied between Ibn Al-Hajib’s approval and disagreement, basing his approval or disagreement on solid foundations, the most important of which are the most famous principles of the linguistic lesson: hearing and analogy.